The Malaysian public's awareness of S&T - Mohd. Asraf, Ratnawati; Sheikh Ahmad, Ismail; Abu Kassim, Noor Lide; Ssekamanya, Siraje Abdallah; Tunku Ahmad, Tunku Badariah; Nik Abdul Rahman, Nik Suryani (2011)
Science and technology are increasingly influencing the way society operates. New discoveries in science and technology are changing the social, ethical, political, and economic structures all over the world. Today, rich countries are not those endowed with abundant natural resources, but those which have managed to harness their human resources to produce innovations and solutions in the areas of science and technology. Hence, it is paramount importance to promote scientific knowledge and a scientific culture among citizens for any country that wants to be relevant in today’s world. Given the importance of science and technology for the progress of our country, a nationwide survey was conducted using 18, 447 respondents randomly selected and stratified according to zone, location, ethnicity, gender, and age to address the following questions. How aware is the Malaysian public of S&T issues? What is the public’s understanding of various S&T issues? How interested are they in S&T? What are their attitudes towards S&T? The study discusses the findings, including an international comparison of how Malaysia compares with other countries on the above issues.